Awakening Leviathan: The effect of democracy on state capacity. (May 2018) - Wang, Erik H.; Xu, Yiqing
Recent debates over the relative importance of democracy and state capacity for human development have led to the prevailing view that a strong state must be built before the introduction of democracy. Our research challenges this "sequencing approach" in international development. Using a global panel of countries over 50 years, we document that democracy has a substantial, positive causal effect on state capacity with identification strategies that adjust for pre-treatment dynamics. The state-enhancing effect of democracy is robust to alternative measures of key variables, a large set of time-varying confounders and an instrumental variable design that leverages variation in regional democratic diffusions. Subsequent analysis suggests contestation, rather than participation, as a potential causal mechanism. Our findings contribute to the burgeoning literature on sources of state capacity in the developing world and yield practical implications for democracy assistance.